Perception of Cantrang Fishermen to the Minister of Marine and Fishery Regulation Number 2 / 2015 - Yuyun Suprapti; Rudianto Syamsu Dhuha; Miftachul Munir (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
Regulation of the Minister of Marine Affairs and Fisheries No. 2 / 2015 about the prohibition of the use of cantrang in the State Fishery Management Area of the Republic of Indonesia is an effort of the Government to anticipate the destructive fishing, namely environmental damage and decrease of fish resources. The purpose of this research is to know repulsion and acceptability of cantrang fisherman to that Regulation. This descriptive research uses data collection techniques through surveys, interviews and documentation, and using questionnaires. This regulation has an impact on the cantrang fishing vessel should not operate, this causes unemployment for the crew, if the government implements that regulations then every ship does not require many crew. The existence of the prohibition of the use of cantrang nets cause increasing of the unemployment rate, when someone does not work it means that income begins to be hampered. On the other hand, the Regulation has a positive impact for the future in the form of sustainable of marine ecosystem. Keywords: perception, fishermen, fisheries and marine minister regulation no 2/2015, cantrang